Comparison between treadmill and bicycle ergometer exercise tests in mild-to-moderate hypertensive Nigerians - Abiodun OO; Balogun MO; Akintomide AO; Adebayo RA; Ajayi OE; Ogunyemi SA; Amadi VN; Adeyeye VO (Dove Medical Press, 2015)
Olugbenga O Abiodun, Michael O Balogun, Anthony O Akintomide, Rasaaq A Adebayo, Olufemi E Ajayi, Suraj A Ogunyemi, Valentine N Amadi, Victor O Adeyeye Cardiology Unit, Department of Medicine, Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Osun state, Nigeria Background: Comparative cardiovascular responses to treadmill and bicycle ergometer (bike) exercise tests in hypertensive Nigerians are not known. This study compared cardiovascular responses to the two modes of exercise testing in hypertensives using maximal exercise protocols. Methods: One hundred and ten male subjects with mild-to-moderate hypertension underwent maximal treadmill and bike test one after the other at a single visit in a simple random manner. Paired-sampled t-test was used to compare responses to both exercise tests while chi-squared test was used to compare categorical variables. Results: The maximal heart rate (P<0.001), peak systolic blood pressure (P=0.02), rate pressure product (P<0.001), peak oxygen uptake (P<0.001), and exercise capacity (P<0.001) in metabolic equivalents were significantly higher on the treadmill than on the bike. Conclusion: Higher cardiovascular responses on treadmill in Nigerian male hypertensives in this study, similar to findings in non-hypertensives and non-Nigerians in earlier studies, suggest that treadmill may be of better diagnostic utility in our population. Keywords: maximal exercise, treadmill, bicycle ergometer, hypertension, Nigerians